FOOD ACIDS AND THEIR EFFECT ON PRODUCT QUALITY (Intent Research Scientific Journal, 2024)
This article discusses food acids and their effect on product quality; substances that change the structure and physico-chemical properties of food products. This group of food additives may include the following substances that change the rheological properties (consistency) of food products: thickeners, jelly-forming and jelly-forming substances, nutrient surfactants, stabilizers of the physical condition of food products, dispensers. The chemical nature of the food additives included in this group is diverse. These include products created by nature and obtained artificially, including through chemical synthesis. These also include connections and individual connections.